Development Model of Agriculture + Travel Industry Integration in the Context of Big Data Explore: A case study from Huyi District, Xi’an - Wang, Pei Chao; Kou, Xiang Ying; Zheng, Yuan (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: The new industrial model of agriculture + tourism has been developed for quite some time, however, in the rapid development of information technology, especially the algorithm is further integrated into the agriculture and tourism industry, this fusion industry has ushered in a new round of development opportunities, but with the development of human society, the traditional model of agriculture and tourism will be gradually eliminated. OBJECTIVES: This paper is aimed at developing the regional needs of agriculture + tourism industry, using advanced big data technology and algorithmic technology to follow the pace of the times, in-depth understanding of the current social needs of agriculture + tourism, so as to better develop their own industries. METHODS:Through the algorithmic technology to analyze the agro-tourism model that is currently being developed in Xi’an, to analyze the problems that arise in the process of its development, and to use the background of big data and clustering algorithmic technology to put forward the corresponding targeted improvement strategies. RESULTS: Utilizing Shuangyi District in Xi’an City as a case study to apply the theory and explore new development paths. CONCLUSION: Shuangyi District, Xi’an City, is rich in soil and water resources, so it has a high level of agricultural development and a favorable geographic location, and also has a huge potential market in tourism. With the support of big data technology, the analysis of the current market demand and the development of local natural and human resources on the basis of maximizing the preservation of the original ecology can promote the development of the local economy.